To study the usefulness of islanded tongue flap reconstruction for carcinoma buccal mucosa defect - Prem Shanker; Mohd Athar; Singh, Sujeet (Asian Journal of Medical Sciences, 2023)
Background: Carcinoma buccal mucosa is very prevalent among the Indian population. The mainstay of treatment is surgical excision, which leaves tissue defects requiring reconstruction. Various techniques and flaps have been used for reconstruction of such defects, and research is still underway for better cosmesis and functional outcomes. Aims and Objectives: The aims of this study were to assess the usefulness of an islanded tongue flap in buccal mucosa cancer defect reconstruction after segmental mandibulectomy. Materials and Methods: The present hospital-based observational study was conducted on patients with carcinoma buccal mucosa, with an age greater than 20 years and both sexes included after obtaining written and informed consent. The patients underwent islanded tongue flap reconstruction after wide local excision of tumor and segmental mandibulectomy. Results: Twenty-four patients underwent the procedure and were included in this study. The outcome of the surgery was compared in terms of deglutition and difficulty in speech on a scale of good, satisfactory, and poor. The cosmetic outcome was also compared in the same way. During the post-operative period, eight (33.33%) patients developed early complications of hematoma and pus discharge. Three (12.5%) developed wound dehiscence. Two (8.33%) of these patients also developed flap necrosis. All these complications were managed conservatively. Overall, the surgery had a good cosmetic outcome with minimal difficulty in deglutition or speech. Conclusion: Based on results, an islanded tongue flap can be regarded as a good alternative for small and medium-sized buccal mucosa cancer defect reconstruction after segmental mandibulectomy.